1988
DOI: 10.1128/jcm.26.9.1757-1762.1988
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of peritonitis in patients on continuous ambulatory peritoneal dialysis

Abstract: The clinical course and laboratory diagnosis of peritonitis in patients undergoing continuous ambulatory peritoneal dialysis was studied in 32 consecutive episodes. Peritonitis was associated with a failure in aseptic technique in eight episodes and with an exit-site infection in four episodes. Intraperitoneal vancomycin and ceftazidime were safe, effective, and convenient. Most patients administered their antibiotics at home, and symptoms usually resolved by day 4. Culture of the deposit obtained by centrifug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…In this study, we did not add any lytic or anti-phagocytic agents before centrifugation, which has previously been shown to yield more positive results. 6,7 Centrifugation without lysis has been shown to give unsatisfactory results in the past, as the intracellular sequestration of microbes may be an important cause of false-negative results.…”
Section: Aetiology Of Capd Peritonitis In Southern Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not add any lytic or anti-phagocytic agents before centrifugation, which has previously been shown to yield more positive results. 6,7 Centrifugation without lysis has been shown to give unsatisfactory results in the past, as the intracellular sequestration of microbes may be an important cause of false-negative results.…”
Section: Aetiology Of Capd Peritonitis In Southern Indiamentioning
confidence: 99%
“…1,3 The sensitivity of the plate culture approach is low and it is observed that peritonitis with negative culture may be high at approximately 50%. 1,[4][5][6][7][8] The sensitivity can be improved by increasing the volume of dialysate to at least 10 mL and also by maybe using automated blood culture systems. 9 Various authors have reported an increase in sensitivity to almost 70-75% by using automated blood culture systems.…”
mentioning
confidence: 99%
“…The method chosen should include an enrichment broth with antiphagocytic and lytic properties (3,18,19). Both centrifugation (12,13,20) and filtration (11)(12)(13)(14)20) have been tested as means of concentrating bacteria from CAPD effluents. Semiautomated blood culture systems have been used for the detection of peritonitis in CAPD effluents.…”
mentioning
confidence: 99%
“…Because of the low concentration of microorganisms in the dialysate, tinctorial sensitivity compared with that of culture results has been reported to range only between 10 and 50% (36,68,90,115,116). Gram-positive organisms may have a higher chance of being detected on Gram stain than gram-negative ones (82). Positivity rates of Gram stains increase with the cellularity of the effluent (90) and decreases after the initiation of antimicrobial therapy (89).…”
Section: Microbiological Findingsmentioning
confidence: 99%
“…Another reason is the presence of antibiotics in the peritoneal cavities of patients under treatment, as exemplified by the lower yield of cultures in such patients (57,89,148). A third reason is intracellular survival of and surface tension between bacteria, which account for the fact that positivity rates of cultures are higher when WBC lysis precedes culture (50, 82,136). Fourth, patients with eosinophilic peritonitis (46) and peritonitis caused by endotoxin (one report; 61) are symptomatic and show increased numbers of WBCs but are culture negative.…”
Section: Microbiological Findingsmentioning
confidence: 99%